Путешествие по чужим столам - Григорьева Александра Александровна (Другой другие о других, 2012)
Экземпляры: Ф 27 (02.06.2014) / Инвентарный номер: 90762 / Цена: 150 / Авт.знак: Г 84 / ГРНТИ: 17.82.31 / ББК: 84(2Рос-Рус)6-4